Investigation on microstructures, hardness, friction, and wear of cold sprayed Ti6Al4V coatings with coating thickness of 100-3000 µm - Khun, Nay Win (2024)
The effect of coating thickness (CT) on the microstructures, hardness, and wear of cold sprayed Ti-6Al-4V (CS-Ti64) coatings was systematically investigated since the prolonged high pressure CS deposition could change their microstructures and porosity levels. In addition, the CT was relatively important for their durability, performance, and service life. Therefore, the CS-Ti64 coatings with different CT of 100-3000 µm were prepared on commercially available Ti64 (CA-Ti64) substrates via high pressure CS processes. The CS-Ti64 coatings had low porosity levels wherewith severely deformed Ti64 particles with a crescent-shape could be seen in their cross-sectional microstructures. The hardness of the CS-Ti64 coatings increased with increased CT probably due to their lowered bulk porosity levels associated with longer high pressure CS deposition. As a result, the increased CT from 100 to 3000 µm resulted in a 9.8% decrease in the wear of the CS-Ti64 coatings. The wear of the CS-Ti64 coating with 3000 µm was 16.8% lower than that of the CA-Ti64 as all the CS-Ti64 coatings had lower wear than the CA-Ti64. It could be concluded that the prolonged high pressure CS deposition for the thick CS-Ti64 coatings had an influence on their porosity, hardness, and wear.